A new record in Argentina and lectotypification of Stromanthe boliviana K. Schum. (Marantaceae) - Zanotti, Christian A.; Ospina, Juan C.; Martín, Claudia M. (Phytotaxa, 2017)
Stromanthe boliviana is recorded for the first time in northwestern Argentina. This species is lectotypified, and a complete morphological description, illustration, and pictures are provided